A sub-1V 78-nA bandgap reference with curvature compensation. (May 2017) - Luo, Ziyang; Lu, Yan; Huang, Mo; Jiang, Junmin; Sin, Sai-Weng; U, Seng-Pan; Martins, Rui P.
Abstract: This paper presents a low power bandgap reference (BGR) with 573 mV average output voltage and 0.95-V minimum supply voltage. Here, the resistor ratio of two types of resistors that have opposite temperature coefficient (TC) realizes a second-order curvature compensation. In addition, to reduce the supply voltage we adopt a voltage divider, and we also employ proportional to absolute temperature (PTAT) voltage generators to reduce the resistor values for low power applications. The proposed BGR fabricated in 65-nm CMOS achieves an average TC of 57 ppm/°C from 0 to 100 °C with 8 samples. The power dissipation at room temperature is 78 nA and the power supply ripple rejection (PSRR) is −67 dB at DC with 1.2 V supply.